Navigating national and religious restrictions relating to marriage formation or dissolution and their effects in Qatar - Noora Al-Saai (23771235) (2025)
Legal pluralism has been explored in several Arab countries, but the Gulf remains understudied, especially concerning practices like strategic religious conversion and unregistered marriages. This study examines how various actors in Qatar, including litigants, judges, and the executive, account for legal or normative pluralism when navigating national or religious restrictions on marriage formation and dissolution. It focuses on court judgments from past and current courts, revealing two practices and the courts’ interpretations of them: strategic religious conversion, and unregistered marriages between foreign nationals and between Qatari-foreign couples. The study argues that informal marriages serve as a legal alternative for the former group and a religious alternative for the latter. By exploring how tensions between state law and Sharīʿa are negotiated; especially regarding the interpretation and establishment of marriage or divorce and their impact on paternity and related rights, it highlights areas where the legacy of Sharīʿa courts persists and areas where judicial independence has been limited, leading to greater cooperation with the executive. By comparing the responses of actors to those in neighboring Bahrain, the study identifies opportunities for expanding judicial autonomy in contemporary Qatar in cases involving the executive’s interests. Other Information Published in: Legal Pluralism and Critical Social Analysis License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/27706869.2025.2592445